2008
DOI: 10.1063/1.2830023
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in a-plane GaN crystal quality by a two-step growth process

Abstract: Nonpolar (112¯0) a-plane GaN films have been grown by metal-organic vapor deposition on r-plane (11¯02) sapphire. Lateral growth is favored using a low V:III ratio resulting in films with a smooth surface, while pitted films are grown at a high V:III ratio indicating preferential on-axis growth. High-resolution x-ray diffraction analysis of both film types showed a strong anisotropy in the peak width of the symmetric omega rocking curve with respect to the in-plane orientation, phi. In-plane isotropic behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
103
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(109 citation statements)
references
References 14 publications
3
103
3
Order By: Relevance
“…Therefore, the smaller FWHMs of (1120) ω-scans in the c-axis direction that were found in this study may also be attributed to the highly elongated a-plane GaN mosaic along the c-axis. Consequently, the lowest in-plane anisotropy (79 arcsec) of (1120) ω-scan widths in sample AG4 is explained by the relatively isotropic size of coherently scattering domains, which results from the reduction in TD/PD density caused by an increase in the 3D-2D growth transition stage, as reported by Hollander et al [18]. Accordingly, deposition conditions in the SiN x interlayer affect both defect density and mosaicity, and therefore, they also influence the size of the coherent scattering domain along the in-plane directions in a-plane GaN films.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…Therefore, the smaller FWHMs of (1120) ω-scans in the c-axis direction that were found in this study may also be attributed to the highly elongated a-plane GaN mosaic along the c-axis. Consequently, the lowest in-plane anisotropy (79 arcsec) of (1120) ω-scan widths in sample AG4 is explained by the relatively isotropic size of coherently scattering domains, which results from the reduction in TD/PD density caused by an increase in the 3D-2D growth transition stage, as reported by Hollander et al [18]. Accordingly, deposition conditions in the SiN x interlayer affect both defect density and mosaicity, and therefore, they also influence the size of the coherent scattering domain along the in-plane directions in a-plane GaN films.…”
Section: Resultssupporting
confidence: 51%
“…A 150-nmthick GaN nucleation layer (NL) was grown on r-plane sapphire substrates at high temperatures. After growing the NL, two buffer layers (BL1 and BL2) were grown for all samples at 1050ºC using a well-known two-step growth method to improve crystalline quality [18]. For the control sample (AG1), which did not contain a SiN x layer, the first a-plane GaN buffer layer (BL1) of ~1 μm was directly grown on the GaN NL at a reactor pressure of 600 mbar and a V/III ratio of 900.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the insertion of in situ Si x N y nanomasks is a well-established method to reduce the density of structural defects in conventionally grown c-plane GaN [7] as well as in heteroepitaxially grown a-plane GaN [8,9].…”
mentioning
confidence: 99%
“…1(b). It has been reported that low growth pressure and low V/III ratio is favorable for two-dimensional (2D)-like growth, while the high ratio leads to easier growth of threedimensional (3D)-like structures [12]. However, in this experiment the results show an interesting feature.…”
Section: Surface Morphology Of A-gan Filmsmentioning
confidence: 57%